Detection and traceability of tetramethylpyrazine in the brewing process of Fuhexiangxing Baijiu - XUE Xijia, CHENG Wei, CHEN Xuefeng, LAN Wei, LI Na, LI Ruilong, PAN Tianquan, DAI Sen (Zhongguo niangzao)
In this study, a method was established for the determination of tetramethylpyrazine (TTMP) in the brewing process of Fuhexiangxing Baijiu by headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS), the distribution and migration of TTMP in the brewing process of Baijiu were traced by analyzing the content of TTMP in Jiuqu, fermented grains (distiller's grains), pit mud and base liquor in different fermentation layers during brewing. The results showed that the optimal detection conditions were volume fraction of ethanol extract 20%, NaCl addition 1.6 g, and headspace solid-phase microextraction time 40 min. Under the optimized conditions, TTMP had a good linear relationship in the mass concentration range of 2.0-50 ng/ml, the correlation coefficient R2 was greater than 0.999, the average adding standard recovery rate was 81.0%-112.5%, and the relative standard deviation (RSD) of precision test results was less than 10%. The analysis results of the TTMP contents during the brewing process showed that the TTMP content in the stacked fermented grains was 61.41 μg/kg, which was mainly originated from high- temperature Daqu and distiller's grains. The highest TTMP contents were found in the upper and middle layers of fermented grains after fermentation, with 220.01 μg/kg and 221.19 μg/kg, respectively, which was mainly originated from high-temperature Daqu, medium-temperature Daqu, distiller's grains, and stacked fermented grains. The TTMP content in base liqor from middle-layer fermented grains was the highest (1 235.80 μg/L), which originated from the fermented grains.